Contribution of Principal Leadership Style and Work Motivation to State Elementary School Teacher Performance in Ampek Nagari Sub-District - Yulvita, Meri; Anisah, Anisah; Gistituati, Nurhizrah; Alkadri, Hanif (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The research started with teacher problems in carrying out learning activities in schools. The research objective was to determine the contribution of the principal's leadership style to teacher performance, the contribution of work motivation to teacher performance, and the contribution of the principal's leadership style and work motivation together to teacher performance. This research is quantitative research with a descriptive approach. The population of this study were all teachers of public elementary schools in Ampek Nagari District, totaling 215 people from 23 schools. The sampling technique used the Cochran formula with an error rate of 5%, so a sample of 85 people was obtained. The instrument is used by distributing questionnaires on a Likert scale. The data obtained were analyzed with the help of SPSS version 25.0. The results of the descriptive analysis of teacher performance are 66.67%, the principal's leadership style is 67.08% and work motivation is 66.62%. The results of the data analysis show that there is a contribution of the principal's leadership style to teacher performance by 27.2%, there is a contribution of work motivation to teacher performance by 32%, there is a contribution between the principal's leadership style and work motivation together on teacher performance by 42 .4%.